Evaluation of roof slope and exposure with different roofing materials in reduced models of animal production facilities in spring and summer - Melo, Thiago V.; Furlan, Renato L. [UNESP]; Milani, Adhemar P. [UNESP]; Buzanskas, Marcos E. [UNESP]; Mota, Diego A. (Associação Brasileira de Engenharia Agrícola, 2014)
The present study was conducted at the Department of Rural Engineering and the Department of Animal Morphology and Physiology of FCAV/Unesp, Jaboticabal, SP, Brazil. The objective was to verify the influence of roof slope, exposure and roofing material on the internal temperature of reduced models of animal production facilities. For the development of the research, 48 reduced and dissemble models with dimensions 1.00 × 1.00 × 0.50 m were used. The roof was shed-type, and the models faced to the North or South directions, with 24 models for each side of exposure. Ceramic, galvanized-steel and fibro tiles were used to build the roofs. Slopes varied between 20, 30, 40 and 50% for the ceramic tile and 10, 30, 40 and 50% for the other two. Inside the models, temperature readings were performed at every hour, for 12 months. The results were evaluated in a general linear model in a nested 3 × 4 × 2 factorial arrangement, in which the effects of roofing material and exposure were nested on the factor Slope. Means were compared by the Tukey test at 5% of probability. After analyzing the data, we observed that with the increase in the slope and exposure to the South, there was a drop in the internal temperature within the model at the geographic coordinates of Jaboticabal city (SP/Brazil).

O presente trabalho foi desenvolvido junto aos Departamentos de Engenharia Rural e Morfologia e Fisiologia Animal da FCAV/Unesp, Jaboticabal - SP. Objetivou-se verificar a influência da inclinação , exposição e cobertura sobre a temperatura interna de modelos reduzidos de instalações zootécnicas. Para o desenvolvimento da pesquisa, foram utilizados 48 modelos reduzidos e dissimilares nas dimensões de 1,00 × 1,00 × 0,50 metros. A cobertura foi de uma água, dispostos nas exposições norte-sul, sendo 24 modelos na exposição norte e 24 na sul. Foram utilizadas, na cobertura, telha de cerâmica, aço galvanizado e fibrocimento. As inclinações variaram de 20; 30; 40 e 50% para telha de cerâmica e 10; 30; 40 e 50% para as demais. No interior dos modelos, foram realizadas leituras de temperatura, de hora em hora, durante 12 meses. Os resultados obtidos foram avaliados num modelo linear geral, no esquema fatorial aninhado 3 × 4 × 2, em que foram considerados: tipo de telha, grau de inclinação e exposição, onde os efeitos de cobertura e exposição foram aninhados no fator inclinação. As médias obtidas foram comparadas pelo teste de Tukey, a 5% de probabilidade. Após a análise dos dados, observa-se que, com o aumento da inclinação na exposição sul, houve decréscimo da temperatura interna no interior do modelo, nas coordenadas geográficas da cidade de Jaboticabal.
Avaliação da inclinação e exposição de telhado em diferentes materiais de cobertura em modelas reduzidos de instalações zootécnicas na primavera e verão
Keywords: Ambience; Heat; Shed; Ambiência; Calor; Galpão